Phosphodegrons in Health and Disease: From Cellular Homeostasis to Therapeutic Potential - Tadashi Nakagawa; Makiko Nakagawa (Kinases and Phosphatases)
Phosphodegrons are critical motifs that play a pivotal role in the regulation of protein stability and function via phosphorylation-dependent signaling pathways. These motifs serve as recognition elements for ubiquitin ligases, facilitating the targeted degradation of proteins. By modulating key cellular processes such as cell cycle progression, DNA repair, and apoptosis, phosphodegrons are essential for maintaining cellular homeostasis. Dysregulation of phosphodegrons has been implicated in a wide range of diseases, including cancer and neurodegenerative disorders, highlighting their potential as therapeutic targets. This review provides an overview of phosphodegron functions along with their biological significance in health and disease. Additionally, we discuss current methodologies for studying phosphodegrons and explore emerging trends in their identification and therapeutic targeting. By synthesizing recent advances in the field, this article aims to offer insights into the future directions and challenges in phosphodegron research, ultimately underscoring their importance in cellular regulation and disease pathology.